Exploring Elementary School English Teachers' Voices in Gaining Students' Attention in Learning - Suryanto, Suryanto; Brawijaya, Ardiless (Journal of English and Education (JEE), 2024)
Student attention plays a pivotal role in learning. It becomes the gateway to learning engagement, behavioral management, and academic achievement. This research investigates several methods elementary school teachers use in Indonesia to capture and maintain students' attention during English language instruction. This study examines the methods and challenges faced in the interaction process, which is crucial for successful learning. The research utilizes a qualitative descriptive study design, including in-depth interviews with three experienced English teachers. The findings indicate that teachers use many interactive and sensory-stimulating methods, including games, total physical response activities, songs, gestures, and visual aids, to attract and hold students' attention. These methods are essential for sustaining involvement and accommodating learning preferences and cultural contexts. However, teachers need more resources, training needs, and a diverse array of students' interests and learning styles, all of which might hinder the execution of these methods. This research emphasizes the need to provide teachers with customized training and resources to use attention-grabbing methods successfully. This study adds to the broader conversation on educational methods in linguistically and culturally diverse settings, indicating that improving teacher support and resources is crucial for promoting successful English language instruction at the elementary school level.